2014
DOI: 10.1016/j.pss.2013.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Escape of the martian protoatmosphere and initial water inventory

Abstract: Latest research in planet formation indicates that Mars formed within a few million years (Myr) and remained as a planetary embryo that never grew to a more massive planet. It can also be expected from dynamical models that most of Mars' building blocks consisted of material that formed in orbital locations just beyond the ice line which could have contained ~0.1–0.20.25emwt.% of H2O. By using these constraints, we estimate the nebula-captured and catastrophically outgassed volatile contents during the solidif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
118
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 91 publications
(132 citation statements)
references
References 93 publications
(211 reference statements)
12
118
0
2
Order By: Relevance
“…Valencia et al (2013) studied the bulk composition and thermal escape of the super-Earth GJ 1214b and other sub-Neptune-type exoplanets by assuming a lowest η hν value of 10% and a highest value of 40%. More or less similar lowest and highest η hν values of 15% and 40% have been assumed in recent works by Erkaev et al (2013), Lammer et al (2013), Erkaev et al (2014), Kislyakova et al (2013Kislyakova et al ( , 2014, and Lammer et al (2014), who studied the escape of hydrogen envelopes from early Mars and sub-Earths to super-Earths inside the habitable zone of a solar-like G-type star for XUV fluxes that are higher than several times to up to 100 times of the presentday Sun, as well as for five exoplanets between the super-Earth and mini-Neptune domain in the Kepler-11 system. Finally, in their recent study on impact-related photoevaporative mass-loss on masses and radii of H 2 O-rich sub-and super-Earths, Kurosaki et al (2014) assumed an η hν value of 10%.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…Valencia et al (2013) studied the bulk composition and thermal escape of the super-Earth GJ 1214b and other sub-Neptune-type exoplanets by assuming a lowest η hν value of 10% and a highest value of 40%. More or less similar lowest and highest η hν values of 15% and 40% have been assumed in recent works by Erkaev et al (2013), Lammer et al (2013), Erkaev et al (2014), Kislyakova et al (2013Kislyakova et al ( , 2014, and Lammer et al (2014), who studied the escape of hydrogen envelopes from early Mars and sub-Earths to super-Earths inside the habitable zone of a solar-like G-type star for XUV fluxes that are higher than several times to up to 100 times of the presentday Sun, as well as for five exoplanets between the super-Earth and mini-Neptune domain in the Kepler-11 system. Finally, in their recent study on impact-related photoevaporative mass-loss on masses and radii of H 2 O-rich sub-and super-Earths, Kurosaki et al (2014) assumed an η hν value of 10%.…”
Section: Introductionsupporting
confidence: 73%
“…This assumption is more or less valid for massive and compact exoplanets (Erkaev et al 2007), such as HD 189733b with an average density ρ ∼ 0.95 g cm −3 , but will yield less accurate mass-loss rates for less compact objects with lower average densities, such as HD 209458b with 0.37 g cm −3 . This effect was first recognized by Watson et al (1981) and was more recently investigated in detail by Erkaev et al (2013Erkaev et al ( , 2014. R XUV can exceed the planetary radius R p quite substantially for a planetary body with a low average density when its atmosphere is exposed to high XUV fluxes.…”
Section: Fig 2 Top Panelmentioning
confidence: 87%
“…Studies related to hydrodynamic escape and evolution of planetary atmospheres (e.g., Sekiya et al 1980aSekiya et al , 1980bSekiya et al , 1981Watson et al 1981;Kasting & Pollack 1983;Yelle 2004;Tian et al 2005aTian et al , 2005bMurry-Clay et al 2009;Koskinen et al 2013;Erkaev et al 2013Erkaev et al , 2014Lammer et al 2013a indicate that the heating of the upper atmosphere caused by high XUV radiation and the related hydrodynamic expansion of the bulk atmosphere is important for the escape of light gases such as hydrogen from early planetary atmospheres. The hydrodynamic outflow of the atmospheric particles is somewhat similar to that of the solar wind described by the well known isothermic model of Parker (1964aParker ( , 1964b.…”
Section: Introductionmentioning
confidence: 99%
“…As described in Erkaev et al (2014) one can assume that dissociation products of H 2 O molecules and CO 2 molecules should also populate the lower hydrogen dominated thermosphere; we apply the same method, discussed in detail in Hunten et al (1987), Zahnle et al (1990), and Erkaev et al (2014), to the loss of these heavier species that are dragged by the dynamically outward flowing bulk atmosphere.…”
Section: Influence On Catastrophically Outgassed Steam Atmospheresmentioning
confidence: 99%
“…Thus, Mars can also be considered as a surviving large planetary embryo whose building blocks consisted of material that formed in orbital locations just beyond the ice line with an initial H 2 O inventory of ∼0.1-0.2 wt-%. Erkaev et al (2014) showed that after the solidification of Mars' magma ocean, a catastrophically outgassed steam atmosphere within the range of ∼50-250 bar H 2 O and ∼10-55 bar CO 2 could have been lost via hydrodynamic escape caused by the high extremeultraviolet (EUV) flux of the young Sun during ∼0.4-12 Myr, if the impact related energy flux of large planetesimals and smaller planetary embryos to the planet's surface prevented the steam atmosphere from condensing.…”
Section: Introductionmentioning
confidence: 99%